2019
DOI: 10.14814/phy2.14064
|View full text |Cite
|
Sign up to set email alerts
|

The effect of the speed and range of motion of movement on the hyperemic response to passive leg movement

Abstract: Passive leg movement ( PLM )‐induced hyperemia is used to assess the function of the vascular endothelium. This study sought to determine the impact of movement speed and range of motion ( ROM ) on the hyperemic response to PLM and determine if the currently recommended protocol of moving the leg through a 90° ROM at 180°/sec provides a peak hyperemic response to PLM . 11 healthy adults underwent … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…Both concentric and eccentric actions were performed during the contraction. The leg was rested at 90 • of knee flexion to minimize the impact that differing degrees of knee flexion have on the blood flow response to knee extension exercise [23]. Since the hyperemic response to knee extension is influenced by the amount of external work performed during a contraction [24,25], the displacement distance of the weight was limited to 15 cm for each contraction.…”
Section: Familiarization Visitmentioning
confidence: 99%
“…Both concentric and eccentric actions were performed during the contraction. The leg was rested at 90 • of knee flexion to minimize the impact that differing degrees of knee flexion have on the blood flow response to knee extension exercise [23]. Since the hyperemic response to knee extension is influenced by the amount of external work performed during a contraction [24,25], the displacement distance of the weight was limited to 15 cm for each contraction.…”
Section: Familiarization Visitmentioning
confidence: 99%
“…In addition to the factors mentioned above, previous research has revealed other factors that must be considered when performing and interpreting tests of vascular function. For example, the placement of the cuff proximal or distal to the site of measurement may impact the results of an FMD test (Doshi et al, 2001), the frequency of movement and the range of motion of PLM (Gifford et al, 2019), and the amount of work performed during ROV (Tschakovsky et al, 2004) have been shown to strongly impact the results. Therefore, these factors should be considered when exploring the relationship between vascular function and other variables, like VȮ 2 max.…”
Section: What Other Factors Influence the Indices Of Vascular Functmentioning
confidence: 99%